Management of Learning Strategies in Elementary Schools During the Covid-19 Pandemic to Maintain Education Quality - Ade Irma Mulyati; Tb. Abin Syamsudin; Ahmad Mudrikah; Cahya Syaodih (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This research was motivated by the unpredictable Covid-19 Pandemic which forced various parties to carry out social distancing and Work from Home (WFH). This condition has an impact on school closures, students learn from home and teachers teach from home. The condition of the Covid-19 pandemic as a new era of Distance Learning. Distance Learning with online/offline/hybrid learning modes as an effort to provide educational services to students. The purpose of this study was to identify and analyze the management of learning strategies in elementary schools during the Covid-19 pandemic to maintain the quality of education. The policy that underlies this research is the Decree of the Minister of Education and Culture Number 719/P/2020 concerning Guidelines for Implementing Curriculum in Education Units in Special Conditions. This research is based on George R. Terry's Theory of Management Functions, according to him “There are 4 management functions, which in the management world are known as POAC; Namely: planning, organizing, actuating and controlling. The approach in this research is a qualitative approach, with a case study type of research method. The research was conducted at Sirnagalih State Elementary School and Al Azhar Syifa Budi Parahyangan Elementary School (ASBP) West Bandung Regency with the research subjects being students. Research results: 1) Schools implement learning strategy management by preparing program plans (materials, strategies, assessments) that are adapted to the Emergency Curriculum and synergize with related parties to carry out learning during the Covid-19 pandemic. 2) Schools have carried out efforts to maintain the quality of education during the Covid-19 pandemic but have not been optimal. This is evidenced by the vast differences between one school and another. On the one hand, there are schools that implement very good distance learning with learning programs and strategies during the Covid-19 pandemic that are well planned by organizing human resources by conducting in-house training, but in other schools distance learning is carried out simply because schools have not establish learning policy guidelines during the Covid-19 pandemic. 3) Implementation of elementary school learning during the Covid-19 pandemic with online/offline/hybrid learning modes. 4) There are several obstacles in primary school learning during the Covid-19 pandemic, including the limitations of studying the Emergency Curriculum with studies on the selection of Core Competencies and Basic Competencies, the fulfillment of facilities and infrastructure, the condition of teachers who when carrying out learning still refers to student books as learning resources. 5) There are solutions to overcome obstacles including schools being required to improve teacher competence to be technology literate, designing adaptive curricula and facilitating adequate infrastructure, as well as Hybrid Learning with visiting teachers (Jarunjung). The conclusion of this study is that the management of learning strategies in elementary schools during the Covid-19 pandemic to maintain the quality of education has been attempted by implementing Distance Learning both online/offline/hybrid learning, but the results have not been optimal.